Kinematics of the active West Andean fold‐and‐thrust belt (central Chile): Structure and long‐term shortening rate. Issue 2 (22nd February 2017) - Riesner, M.; Lacassin, R.; Simoes, M.; Armijo, R.; Rauld, R.; Vargas, G.
Abstract: West verging thrusts, synthetic with the Nazca‐South America subduction interface, have been recently discovered at the western front of the Andes. At 33°30′S, the active San Ramón fault stands as the most frontal of these west verging structures and represents a major earthquake threat for Santiago, capital city of Chile. Here we elaborate a detailed 3‐D structural map and a precise cross section of the West Andean fold‐and‐thrust belt based on field observations, satellite imagery, and previous structural data, together with digital topography. We then reconstruct the evolution of this frontal belt using a trishear kinematic approach. Our reconstruction implies westward propagation of deformation with a total shortening of 9–15 km accumulated over the last 25 Myr. An overall long‐term shortening rate of 0.1–0.5 mm/yr is deduced. The maximum value of this shortening rate compares well with the rate that may be inferred from recent trench data across the San Ramón fault and the slip associated with the past two Mw > 7 earthquakes. This suggests that the San Ramón fault is most probably the only presently active fault of the West Andean fold‐and‐thrust‐belt and that most—if not all—the deformation is to be released seismically. Key Points: The 3‐D structural map and geological cross section of the WAFTB east of Santiago Kinematics of deformation deduced from precise mapping of syntectonic Farellones formation Long‐term shortening rate of 0.1–0.5 mm/yr, with possible deceleration by 20 Ma